Factors affecting mortality in trauma patients hospitalized in the intensive care unit - Atlas, Ahmet; Büyükfırat, Evren; Ethemoğlu, Kadri Burak; Karahan, Mahmut Alp; Altay, Nuray (Journal of Surgery and Medicine, 2020)
Aim: An accurate estimation of the prognosis of patients admitted to the intensive care unit (ICU) is of prime importance for their clinical management. The aim of this retrospective study was to investigate factors affecting mortality in trauma patients hospitalized in the ICU. Methods: This retrospective study reviewed medical records of trauma patients who received ICU care at Harran University Medical School Anesthesiology and Reanimation Department between January 2015 and December 2019. Age, gender, comorbidities, Glasgow Coma Scale (GSC), and Acute Physiology and Chronic Health Evaluation 2 (APACHE-II) scores, Revised Trauma Score (RTS), duration of hospital and ICU stay, mortality rate, and brain death rate were reviewed for each patient. Additionally, other factors that could affect the mortality and morbidity of patients, including admission lactate level and the clinical department of referral were evaluated. Results: A total of 155 patients comprised 76.8% men and 23.2% women. Comorbidities were present in 10.3% of the patients. Of all patients, 90.3% had been referred from the emergency service, 8.4% of them from operating theatres, and 1.3% of them from inpatient clinics. Mean duration of mechanical ventilation was 12.3 (28.6) days, mean duration of ICU stay was 8.5 (20.7) days, and the mean duration of hospital stay was 12.9 (21.7) days. Among 155 patients, 123 (79.4%) were discharged (surviving group) and mortality occurred in the remaining 32 (20.6%) patients (non-surviving group). The non-surviving group comprised 68.8% men and 31.2 women. In all patients, mean admission lactate level was 2.9(3.6) mmol/L and mean APACHE-II score was 14.1(7.1). Multivariate analysis indicated that a single unit increase in APACHE-II score increased the mortality risk by 2.45-fold. A significant relationship was found between admission lactate level, APACHE-II score, and mortality (P=0.001 for both). Mean RTS score was 10.1 (2.5) and mean GCS score was 11.7 (4.4). The analysis also indicated that a single unit increase in RTS score decreased the mortality risk by 94%, and a single unit increase in GCS score decreased the mortality risk by 69%. A significant relationship was found between decreased RTS and GCS scores and mortality (P=0.001 for both). Conclusion: Admission GCS, APACHE-II, and RTS scores and admission lactate levels could be useful predictors of mortality and could also be guiding in the determination of prognosis in patients transferred to the ICU due to trauma.